Flood-Irrigated Ridge-Till Corn Cost-Return Budget - Sartwelle III, James D.; Henson, Darl W. (My University, 1997)
This publication provides expected yields and enterprise return for producing flood-irrigated corn under a ridge-till cropping system.
MF969_1997_10
Keywords: MF969; Economics; Crops; MF